Analisis Resiko Derajat Kesehatan Petani Pengguna Pestisida - Denisius Umbu Pati (JURNAL KESEHATAN PRIMER, 2020)
Background: Healthy is a state of well-being in body, soul, and social conditions so that everyone can live productively socially and economically. Objective: to analyze the effect of risk factors for the health degree of pesticide user farmers in Lambanapu Village, East Sumba Regency. Method: This research is an analytic survey with a cross sectional study design. The population in this study were 132 respondents who used pesticide farmers. The sampling technique used was simple random sampling technique. The sample in this study were 80 respondents who used pesticide farmers. Results: Univariate analysis showed the degree of public health with theoretical farmers who were not sick was 30 (37.5%) and sick were 50 (62.5%), knowledge of pesticide user farmers in good categories was 11 (13.8%), moderate numbered 48 (60.0%) and less amounted to 21 (26.3%), education of farmers using pesticides more than strata 1 amounted to 24 (30.0%), SMP and SMA amounted to 43 (53.8%) and less than SD amounted to 13 (16.3%) while personal protective equipment that meets the requirements amounted to 53 (66.3%) and did not meet the requirements amounted to 27 (33.8%). The results of the bivariate analysis showed that there was an influence between knowledge (p = 0.030), education (p = 0.009) and personal protective equipment (p = 0.003) with the degree of public health. Conclusion: There is a significant influence between knowledge, education and personal protective equipment on health status. Latar Belakang: Sehat adalah keadaan sejahtera dari badan, jiwa, dan sosial sehingga memungkinkan setiap orang dapat hidup produktif secara sosial dan ekonomi. Tujuan: untuk Menganalisis Pengaruh Faktor Resiko Derajat Kesehatan Petani Pengguna Pestisida di Kelurahan Lambanapu Kabupaten Sumba Timur. Metode: Jenis penelitian ini adalah survei analitik dengan rancang bangun cross sectional study. Populasi dalam penelitian ini adalah 132 responden petani pengguna pestisida. Teknik sampling yang digunakan teknik simple random sampling. Sampel dalam penelitian ini adalah 80 responden petani penggguna pestisida. Hasil: Analisis univariat menunjukkan derajat kesehatan masyarakat dengan petani keteori tidak sakit berjumlah 30 (37.5%) dan sakit berjumlah 50 (62.5%), pengetahuan petani pengguna pestisida dengan kategori baik berjumlah 11 (13.8%), sedang berjumlah 48 (60.0%) dan kurang berjumlah 21 (26.3%), pendidikan petani pengguna pestisida lebih dari strata 1 berjumlah 24 (30.0%), SMP dan SMA berjumlah 43 (53.8%) dan kurang dari SD berjumlah 13 (16.3%) sedangkan alat pelindung diri yang memenuhi syarat berjumlah 53 (66.3%) dan tidak memenuhi syarat berjumlah 27 (33.8%). Hasil analisis bivariat menunjukkan bahwa ada pengaruh antara pengetahuan (p=0.030), pendidikan (p=0.009) dan alat pelindung diri (p=0.003) dengan derajat kesehatan masyarakat. Kesimpulan: Ada pengaruh yang signifikan antara pengetahuan, pendidikan dan alat pelindung diri terhadap derajat kesehatan.